What Drives Private Equity Investments in Romania? - Precup, Mihai (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
This paper aims at presenting the determinants of private equity investments in Romania over the period 2000 – 2013. Additionally, this paper presents the main highlights in terms of evolution, source of funding and activities in which the private equity funds invested during the crisis. Starting from the existing literature, this paper extends the analysis of private equity drivers to Romanian market by including variables such as: economic growth, market capitalization, interest rate, unemployment rate and public R&D expenditure which were already tested in previous papers. In addition, this paper introduces new variables such us productivity and corruption index which we consider important factors in explaining the evolution of private equity investments in Romania. The results of our empirical model confirmed existing hypothesis regarding the importance of some determinants such as: unemployment rate, economic growth, market capitalization and corruption. Based on our empirical results, we have pointed several strategic directions that are meant to support the development of the private equity market in Romania.